(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Microgrid power distribution systems require robust and adaptive control strategies to maintain stability under challenging operating conditions. This study proposes an advanced Under-Frequency Load Shedding (UFLS) scheme for isolated microgrids by integrating the Analytical Hierarchy Process (AHP) for systematic load prioritization. The method ranks loads based on their criticality and applies staged shedding during under-frequency events. Simulation results in MATLAB/Simulink show that, without the UFLS scheme, the system experiences severe under-frequency, diesel generator overloading, and eventual system failure. In contrast, the proposed UFLS scheme successfully restores frequency to nominal levels, prevents generator overloading, and maintains voltage within ± 5% of nominal values. These results demonstrate the ability of the scheme to enhance system resilience, maintain power quality, and safeguard critical services in isolated microgrids.